PENGEMBANGAN BLOG SUPPORT MATA KULIAH STATISTIKA PENDIDIKAN PERGURUAN TINGGI STKIP MUHAMMADIYAH BANGKA BELITUNG - Yudi Yunika Putra; Adi Saputra (Universitas Sultan Ageng Tirtayasa, 2018)
Blog support based online learning media is learning media that appropriate to the development of time periode, it is because it can be accessed everytime and everywhere, and also it is integrated to social media. Besides that, this blog support learning media makes students feel easy to search about statistics education materials.The aim of this research is to build the product of blog support statistics education subject for university student that has valid and practical has potential efects. This research method used research and Development study. The subjects of this research are the university students in the third semester of PGSD program of STKIP Muhammadiyah Bangka Belitung. The results of this research is the product of blog support learning media that valid and practical and has potential efect to the students, because blog media that is developed is very efective for learning statistics and very appropriate to the development of time period. This blog support can be accessed at http http://www.statistikaonline.com/. Keywoords: Blog Support, Development Studies, Educational Statistics